Metastatic Pheochromocytomas and Abdominal Paragangliomas - Granberg, Dan (J Clin Endocrinol Metab, 2021)
CONTEXT: Pheochromocytomas and paragangliomas (PPGLs) are believed to harbor malignant potential; about 10% to 15% of pheochromocytomas and up to 50% of abdominal paragangliomas will exhibit metastatic behavior. EVIDENCE ACQUISITION: Extensive searches in the PubMed database with various combinations of the key words pheochromocytoma, paraganglioma, metastatic, malignant, diagnosis, pathology, genetic, and treatment were the basis for the present review. DATA SYNTHESIS: To pinpoint metastatic potential in PPGLs is difficult, but nevertheless crucial for the individual patient to receive tailor-made follow-up and adjuvant treatment following primary surgery. A combination of histological workup and molecular predictive markers can possibly aid the clinicians in this aspect. Most patients with PPGLs have localized disease and may be cured by surgery. Plasma metanephrines are the main biochemical tests. Genetic testing is important, both for counseling and prognostic estimation. Apart from computed tomography and magnetic resonance imaging, molecular imaging using (68)Ga-DOTATOC/DOTATATE should be performed. (123)I-MIBG scintigraphy may be performed to determine whether (131)I-MIBG therapy is a possible option. As first-line treatment in patients with metastatic disease, (177)Lu-DOTATATE or (131)I-MIBG is recommended, depending on which shows best expression. In patients with very low proliferative activity, watch-and-wait or primary treatment with long-acting somatostatin analogues may be considered. As second-line treatment, or first-line in patients with high proliferative rate, chemotherapy with temozolomide or cyclophosphamide + vincristine + dacarbazine is the therapy of choice. Other therapies, including sunitinib, cabozantinib, everolimus, and PD-1/PDL-1 inhibitors, have shown modest effect. CONCLUSIONS: Metastatic PPGLs need individualized management and should always be discussed in specialized and interdisciplinary tumor boards. Further studies and newer treatment modalities are urgently needed.